ANALISIS VERBA OROSU SEBAGAI POLISEMI : KAJIAN LINGUISTIK KOGNITIF - Rachmalia Nurbaeti, - (2018)
Suatu kata yang memilikibanyakmaknadanmaknatersebutsalingberkaitandisebutsebagaipolisemi.DalambahasaJepangterdapatbanyakkata yangberpolisemi. Salah satuverba yang berpolisemiadalahverbaorosu.PembelajarbahasaJepangterkadangmerasakesulitanketikamenggunakanataumenerjemahkanverbaorosudalamkalimat.Olehkarenaitupenulismelakukanpenelitianberupaanalisismaknaverbaorosusebagaipolisemi, untukmengetahuimaknaapasaja yang terdapatdalamverbaorosusertahubunganantarmaknanya. Penelitianinimenggunakanmetodeanalisisdeskriptif. Untukmendeskripsikanhubunganantarmaknaverbaorosu, digunakantigamajasyaitumetafora, metonimi, dansinekdoke. Dari hasilanalisis, disimpulkanbahwamaknadasardariverbaorosuadalah①Menurunkan (memindahkanobjekdariataskebawah).Maknaperluasandariverbaorosuyaitu②menurunkanpenumpangdanbarangmuatan, ③menutup, ④menutuptoko, ⑤memberhentikanseseorangdarijabatannya, ⑥memakaiuntukpertama kali ⑦menarikuangdari bank, ⑧menggugurkankandungan, ⑨memotong, ⑩mengiris, ⑪memarut, ⑫tertanam,⑬ mengunci, ⑭ memanggilhalgaib, dan⑮ menjualsecaragrosir. Maknaverbaorosu yang mengalamiperluasansecarametaforaadalahmakna　⑤,⑧, ⑪,⑫, ⑬, dan⑮.Perluasanmakna yang mengalamiperluasansecarametonimiyaitumakna④,⑥.⑦, ⑨, dan⑭Untukperluasanmaknasecarasinekdokeyaitumakna②, ③, dan⑩. ;---A word that has many or several meaning with interrelated meanings referred to as polysemy. In Japanese there are many polysemic words. Japanese learners often find it diffuclt to use or translate orosu in a sentence. Therefore, the authors conducted a study in the form of an analysis of the meaning of orosu as polysemy, to find out meaningsthat contained in the verb and relation of the meanings.This research uses descriptive analysis method. The meanings are described using metaphor, metonymy, and synecdhoce as figurative speech. From the result of the analysis, it is concluded that the basic meaning of orosu is ①to take down object from a higher place. Expanded meanings of orusu are ②to drop off passanger or unload luggage, ③to close, ④to close a store, ⑤remove someone from higher role, ⑥to use something for the first time,⑦withdraw money, ⑧abort a fetus, ⑨to cut, ⑩to fillet, ⑪to grate, ⑫firmly plant, ⑬to lock, ⑭to call spirits, and ⑮sell wholesale.The meanings that expanded into metaphorical expansion are meaning number ⑤,⑧, ⑪,⑫, ⑬, and⑮. The meanings that expanded metonymously are meaning number ④,⑥.⑦, ⑨, and.⑭And the meanings that expanded into synecdoche are meaning number ②, ③,and⑩.